PENGARUH MOTIVASI, KEPUASAN KERJA DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN TOJO UNA-UNA - Rismanto, Rismanto (Katalogis, 2017)
The aims of the study are: 1) to determine and analyze simultaneous influence and partial of motivation, work satisfaction, and HR development on officials’ performance The Agency of Financial Administration and Local Asset of Tojo Una-Una. Type of research is descriptive causal with multiple linear regressions analysis and census sampling technique. Demographic respondents show that 56.8% of 44 officials in this agency is women, 50% of them aged between 20-30, 63.6% hold bachelor degree, and the maximum length of work between 1-5 years. Variable with highest mean of 4.41 is X3 (HR development), while mean of performance is 4.50. The result of multiple linear regressions analysis finds that Fvalue of 7.428 with sig. value of 0.000 on confidence level (α = 0,05). This means that motivation, work satisfaction, and HR development simultaneously have positively and significantly on officials’ performance in The Agency of Financial Administration and Local Asset of Tojo Una-Una. Partially, motivation and work satisfaction have postive and significant influence, while HR development has insignificant influence on officials’ performance in The Agency of Financial Administration and Local Asset of Tojo Una-Una.